2010
DOI: 10.1111/j.1365-2672.2009.04506.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of polymers PVP90 and Ficoll400 on storage stability and viability ofLactobacillus coryniformisSi3 freeze‐dried in sucrose

Abstract: Aims:  To investigate the effect of freeze‐dried Lactobacillus coryniformis Si3 on storage stability by adding polymers to sucrose‐based formulations and to examine the relationship between amorphous matrix stability and cell viability. Methods and Results:  The resistance to moisture‐induced sucrose crystallization and effects on the glass transition temperature (Tg) by the addition of polymers to the formulation were determined by different calorimetric techniques. Both polymers increased the amorphous matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
(83 reference statements)
2
11
0
Order By: Relevance
“…Vacuum dried L. paracasei was reported to be highly stable during storage at 4°C, and no significant inactivation was reported following 3 months of storage. This result is in accordance with studies on storage of freeze‐dried lactic acid bacteria . Comparatively, the inactivation rate constants of cells dried by vacuum drying were lower than those of the same strain dried by freeze‐drying.…”
Section: Vacuum Dryingsupporting
confidence: 90%
See 1 more Smart Citation
“…Vacuum dried L. paracasei was reported to be highly stable during storage at 4°C, and no significant inactivation was reported following 3 months of storage. This result is in accordance with studies on storage of freeze‐dried lactic acid bacteria . Comparatively, the inactivation rate constants of cells dried by vacuum drying were lower than those of the same strain dried by freeze‐drying.…”
Section: Vacuum Dryingsupporting
confidence: 90%
“…This result is in accordance with studies on storage of freeze-dried lactic acid bacteria. 217,218 Comparatively, the inactivation rate constants of cells dried by vacuum drying were lower than those of the same strain dried by freeze-drying. Conrad et al 219 examined the effect of vacuum drying on the stability of Lactobacillus acidophilus (L. acidophilus).…”
Section: Vacuum Dryingmentioning
confidence: 86%
“…It was suggested that in order to achieve nearly complete reduction of molecular movements, amorphous pharmaceutical solids should be stored 50 °C below T g (Hancock and others 1995). Similar findings were reported also in a study with L. coryniformis by Schoug and others (2010) and with L. rhamnosus by Miao and others (2008) where viability of cells clearly decreased at T – T g higher than –50 °C and ca. –30 °C, respectively.…”
Section: Role Of Glassy State During Storagesupporting
confidence: 90%
“…The formulated cell suspensions were freeze dried in a pilot plant freeze dryer (Lyostar II; FTS Kinetics, Stone Ridge, NY, USA) using a previously developed method optimised for freeze drying of sucrose 35. Briefly, 10 ‐mL glass vials were filled with 1–2 mL of the formulated cell suspensions, cooled on the shelf in the freeze dryer at 5 °C min −1 until a temperature of − 50 °C was reached and held isothermally at that temperature for 50 min.…”
Section: Methodsmentioning
confidence: 99%